Tissue-Engineered Skeletal Muscle Models to Study Muscle Function, Plasticity, and Disease - Khodabukus, Alastair (Frontiers in Physiology, 2021)
Skeletal muscle possesses remarkable plasticity that permits functional adaptations to a wide range of signals such as motor input, exercise, and disease. Small animal models have been pivotal in elucidating the molecular mechanisms regulating skeletal muscle adaptation and plasticity. However, these small animal models fail to accurately model human muscle disease resulting in poor clinical success of therapies. Here, we review the potential of in vitro three-dimensional tissue-engineered skeletal muscle models to study muscle function, plasticity, and disease. First, we discuss the generation and function of in vitro skeletal muscle models. We then discuss the genetic, neural, and hormonal factors regulating skeletal muscle fiber-type in vivo and the ability of current in vitro models to study muscle fiber-type regulation. We also evaluate the potential of these systems to be utilized in a patient-specific manner to accurately model and gain novel insights into diseases such as Duchenne muscular dystrophy and volumetric muscle loss. We conclude with a discussion on future developments required for tissue-engineered skeletal muscle models to become more mature, biomimetic, and widely utilized for studying muscle physiology, disease, and clinical use.